Understanding adolescent pregnancy from the perspectives of pregnant adolescents in a Northern Thailand province: a phenomenological study - Leekuan, Panitsara (2020)
Background: Adolescent pregnancy is a global health issue in nursing, medical, and psychological literature, and a significant social and practical concern, particularly in the context of developing countries. Adolescent pregnancy is associated with severe medical health problems commonly affecting socially disadvantaged pregnant adolescents. Existing literature has investigated meanings, factors, and associated outcomes of adolescent pregnancy in order to increase knowledge of the causes of increasing adolescent pregnancy rates. However, few studies have allowed pregnant adolescent women to voice their experiences, express their feelings, and give their own meanings to their pregnancy, and their holistic experiential dimensions and care requirements remain under-researched. As a result of this research gap and the manifest need for improved care for this group, this study explores experiences of pregnant adolescents in Thailand in depth, engaging with a deep-seated interest in adolescent pregnancy issues and narratives, developing the understanding of the situation from the perspective of Thai pregnant adolescents. The aim of this study is to improve understanding and interpretation of pregnant adolescents’ perspectives associated with first-time pregnancy experiences in Northern Thailand.